Red man syndrome during administration of prophylactic antibiotic against infective endocarditis - Ngeow, Wei Cheong; Chai, W.L.; Moody, A.B. (2000)
Red man syndrome (RMS) is the occurrence flushing, pruritus, chest pain, muscle spasm or hypotension during vancomycin infusion. It usually happens as a result of rapid infusion of the drug but may also occur after slow administration. The frequency and severity of this phenomenon diminish with repeated administration of vancomycin. A case is presented whereby RMS occurred while prophylactic antibiotic against infective endocarditis was administered.